2020
DOI: 10.1017/s1431927620024745
|View full text |Cite
|
Sign up to set email alerts
|

Retarding Field Integrated Fluorescence and Electron Microscope

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Bouwer et al ( Bouwer et al, 2017 ) proposed applying a negative bias voltage to the sample to decrease the interaction volume for a given acceleration voltage and improve sectioning capabilities in block-face SEM, where the block face is imaged. More recently, Vos et al (2021) and Lane et al (2021) extended this approach to BSE-imaging of sections in a SEM. Although very useful, this condition is not available to many SEM-users.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bouwer et al ( Bouwer et al, 2017 ) proposed applying a negative bias voltage to the sample to decrease the interaction volume for a given acceleration voltage and improve sectioning capabilities in block-face SEM, where the block face is imaged. More recently, Vos et al (2021) and Lane et al (2021) extended this approach to BSE-imaging of sections in a SEM. Although very useful, this condition is not available to many SEM-users.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, other groups have obtained results with SEM-imaging of similar preparations using different accelerating voltages and instruments, while information on other parameters was sparse or lacking ( Peddie et al, 2014 ; Markert et al, 2016 ; Bouwer et al, 2017 ). More recently, it was shown that biasing the sample can ameliorate SEM-imaging of sections ( Vos et al, 2021 ). In this study, we show how different imaging parameters affect image quality and propose guidelines on how to optimize basic SEM settings in function of section thickness for high-resolution thin-section imaging.…”
Section: Introductionmentioning
confidence: 99%
“…Excitation wavelengths of 405 and 555 nm are used to excite Hoechst and AF594. The SECOM is equipped with a CFI S Plan Fluor ELWD 60XC (0.70 NA) objective (Nikon), which allows for long working distance imaging (1.8–2.6 mm), to prevent electrical breakdown in vacuum, which must be accounted for due to the presence of high electric fields induced by the stage bias ( Vos et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Retarding (or deceleration) fields applied between electron objective lens and sample have been shown to improve imaging contrast in SEM and FIB-SEM, and therefore allow the reduction of heavy metal staining (Lane et al, 2021). Lately, Vos et al (2020) have successfully applied a retarding (or deceleration) field in an integrated fluorescence and SEM setup. Besides technological improvements, new labelling approaches are being explored.…”
Section: Future Perspectivesmentioning
confidence: 99%